Localizing Global Solidarity: Humanitarian Aid in Lesvos - Shults, Lee Michael; Haaland, Hanne; Wallevik, Hege (Frontiers in Political Science, 2021)
The so-called “refugee crisis” in Lesvos, Greece provides a poignant example of situated, local suffering that has called for the coordination of global resources to provide relief. Some of the first to respond were local and international Citizen Initiatives for Global Solidarity (CIGS). While a growing role for CIGS has been interpreted as a call for more global involvement, arguments for the increased localization of relief efforts suggest the need for aid agents to maintain a reflexive awareness of the potential for an influx of outside assistance to disempower those most affected. We argue that barriers to implementing the localization of humanitarian aid can be better understood by positioning this localization alongside theories of global solidarity. This paper pairs theoretical contributions from the fields of moral and political philosophy with an analysis of interview material gathered in Lesvos between 2015 and 2019. Our goal is to use narratives of conflicting interests in Lesvos to explore conceptual distinctions concerning solidarity and emphasize the importance of the localization of global solidarity in humanitarian aid. We conclude that while global solidarity represents a demanding effort to identify with distant others and provide aid, the intensity and transformative potential of the process of “making the crisis one’s own” through solidary engagement can overshadow the importance of local ownership of crisis management.